2022
DOI: 10.1007/s40194-022-01412-3
|View full text |Cite
|
Sign up to set email alerts
|

Dissimilar micro beam welding of titanium to Nitinol and stainless steel using biocompatible filler materials for medical applications

Abstract: In the present investigation, thin sheet geometries of commercially pure titanium (cp, grade 4) are butt-welded to AISI 316L stainless steel as well as Nitinol by means of micro electron beam welding using filler materials. In order to avoid mixing of the base materials, the refractory metals tantalum, niobium and hafnium are applied as intermediate layers. Owing to the biocompatibility of these filler materials, the final products are suitable for medical technology applications. In combination with low energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Dissimilar welded joints have the potential to combine the individual properties of different metals and, thus, generate various functional and economic advantages. In particular, hybrid parts made of commercially pure titanium (cp-Ti) and stainless steel are of high relevance in manifold industrial sectors, for example, the chemical, energy, and medical technology industries [1,2]. However, dissimilar fusion welding of cp-Ti to stainless steel is limited by thermophysical and chemical incompatibilities [1,3].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dissimilar welded joints have the potential to combine the individual properties of different metals and, thus, generate various functional and economic advantages. In particular, hybrid parts made of commercially pure titanium (cp-Ti) and stainless steel are of high relevance in manifold industrial sectors, for example, the chemical, energy, and medical technology industries [1,2]. However, dissimilar fusion welding of cp-Ti to stainless steel is limited by thermophysical and chemical incompatibilities [1,3].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the aforementioned material combinations do not exclusively involve biocompatible materials and are consequently unsuitable for medical technology applications. In a recent study by Wiegand et al [2], pure Nb was identified as a promising interlayer material for dissimilar welding of cp-Ti to stainless steel. By micro-electron beam welding, it was possible to achieve tensile strengths of up to 394 MPa in butt joint configuration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It`s implementation makes it possible to increase the installation and repair work manufacturability. Refractory metals such as vanadium [8][9][10][11][12][13][14], niobium [15][16][17][18][19][20][21][22][23] and tantalum [10,15,24,25] can be used for deposition on titanium alloy during additive forming. However, the use of tantalum may cause technological problems due to the large difference in melting temperatures.…”
mentioning
confidence: 99%
“…However, according to scienti c papers [12,13,33,34], the formation of unfavourable ω-phase is revealed only in the Ti-V system. In the Ti-Nb system the formation of ω-phase is not observed [15,[16][17][18][19][20][21][22][23]. In addition to the formation of ω-phase, the creation of the unmixed region with zones of high and low titanium content is an important feature of the Ti-V system [14].…”
mentioning
confidence: 99%